Os jogos de análise fonológica e o desenvolvimento da compreensão do sistema de escrita alfabética pelas crianças - Simone Regina Pinto Pereira (2024)
This intervention research sought to analyze the learning path of two groups of children during sessions with phonological analysis games, one group performing a writing systematization activity after the game and the other group without writing systematization. Two questions guided this study: will the children who participated in intervention sessions with phonological analysis games advance in their hypotheses about alphabetic writing? Will there be a difference in the advancement of hypotheses between a group of children who participated in sessions with games and another who participated in sessions with games that will involve a moment of systematization with the presence of writing? The study included 12 6-year-old children from the same 1st grade class of a municipal school in Belo Horizonte, who were in the pre-syllabic phase of writing. To organize the groups, an initial diagnostic assessment of writing, letter knowledge and phonological knowledge was carried out using the CONFIAS test (Phonological Awareness Sequential Assessment Instrument). Considering the results of the skills of knowledge of letters and phonological awareness evaluated, three groups were organized, consisting of 4 children, experimental group 1 that participated in 8 sessions with phonological analysis games, experimental group 2 that participated in the same sessions, and after the game experienced a moment of written record with words explored in the game and group 3 that represents the control group, that is, pre-syllabic children from the same class who did not participate in the sessions with games. The games chosen for the interventions sought to mobilize different levels of phonological skills and in the sessions, moments were provided for reflection, analysis and collective discussion for both groups, with the adult being the mediator of the process. For data collection, the children's written records (diagnostic evaluations) and video recordings of the sessions were used. By analyzing the data collected, it was identified that the use of games favored metalinguistic reflections, interaction, and motivation for learning the written language, and there was also progress in the understanding of the alphabetic principle by the children. The analyses performed and the data collected showed that the children participating in experimental group 1 and experimental group 2 advanced more in their writing conceptualization process than the control group. The children in experimental group 2 presented more pertinent correspondences between letter and sound, corroborating the perspective that the systematization of writing, i.e., exploring the graphophonic correspondences after the moment of the game, enhanced learning. Based on the experiences and data of the research, an e-book for teachers was elaborated as an educational resource, with suggestions for phonological analysis games, indicating possibilities of mediations and writing systematization activities to be carried out after the games.